Philosophy - Doepke, Frederick
PHILOSOPHY: CONFRONTING THE UNAVOIDABLE is a broad yet highly coherent presentation of philosophy in a story-like format, linking successively issues in logic (which, using the Kantian taxonomy, includes epistemology), metaphysics, ethics, and social philosophy. This book avoids the technical issues that are of interest only to specialists by following the theme suggested in the title, that philosophy deals centrally with the kinds of commitments made just by living a human life. With a continuously unfolding exposition of all the main areas of philosophy that is unified by the contention that philosophy is of primary value to everyone, this text provides a clear sense of direction that should deepen class discussions and enhance interest in these essential issues